Mediating effects in the structural equation model of Malaysian public service competitiveness - Syahrul Idzuan Mohamad,; Nur Riza Mohd Suradi,; Faridatulazna Ahmad Shahabuddin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
These days, public service performance is determined by competitiveness. Due to a prolonged period of stagnation, Malaysia’s competitive performance is at a critical level. The public service is therefore under pressure to demonstrate that all policies and programs are highly valued. This study aims to determine the primary variables influencing the ability of Malaysia’s public services to compete. Data were acquired through surveys completed by 373 respondents from 26 ministries. The relationships between talent management, human capital, and competitiveness were analysed using structural equation modelling. The results indicate a significant and positive relationship between talent management and competitiveness, with human capital serving as a significant partial mediator. This study highlights the direct importance of talent management for public services competitiveness and its indirect impact through human capital. These insights can assist policymakers in developing a strategic framework to keep the Malaysian public service competitive.